Glial-Plug Proliferation after Inverted Internal Limiting Membrane Flap Technique for Idiopathic Macular Hole. (30th September 2022) - Cisiecki, Sławomir; Bonińska, Karolina; Dybek, Tomasz; Bednarski, Maciej
Abstract : Purpose . This study aimed to analyze the effect of multiple folded internal limiting membrane (ILM) flap in the inverted ILM flap technique on postoperative outcomes of patients with full-thickness macular hole (FTMH). Methods . This retrospective study included 41 eyes of 41 patients with FTMH treated with vitrectomy using the inverted ILM flap technique. Complete ophthalmic examination was performed preoperatively, at 1 week, and at 1, 3, 6, 9, and 12 months after surgery. Results . Postoperative SD-OCT confirmed macular hole (MH) closure in all patients. The mean BCVA improved from 0.7 LogMAR (20/100) preoperatively to 0.5 LogMAR (20/63) postoperatively. In two cases, 7 days after vitrectomy, flap closure was noted. At the final visit after 12 months, the following foveal contours were noted: 14 U-shape (34.1%), 12 irregular (W-shape) (29.3%), and 6 V-shape (14.6%). We observed a type of "plug closure" in 9 (22%) eyes in which hyperproliferation was noted in one eye. Conclusions . The surgeons should be aware of potential hyperproliferation on the retinal surface after the multi-layered flap technique.